Teacher’s Strategies and Technique in Teaching Speaking - Aritonang, Juni Jeffri; Manik, Sondang; Sipayung, Kammer (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Speaking is a topic that has relevance for all of us. As an important component in direct spoken language processing. Speaking is also an area that is interconnected with numerous areas of inquiry and development. The research was done through an experimental design using one-way ANOVA. The population of the research was tenth grade students of SMA Negeri 1 Rantau Utara which consisted of 148 students while the samples were class X-I as the experimental group A,Â  X-II as the experimental group B andÂ  X-IV2 as the control group which consisted 90 students. The data were taken by using instrument or test. After validating the test, the researcher gave the pre-test to both classes to examine the normality and homogeneity of the data. It would be good for us to know about the testing criteria in the ANOVA TEST. If the value is significant or the (P Value) is less than 0.05 then we can conclude that there is a significant difference. And if the significance value or (P Value) is greater than 0.05 then it can be concluded that there is no significant difference. Based on the data analysis in speaking skill through this Cognitive and Dictogloss Strategies in SMA Negeri 1 Rantau Utara. Both of the strategies provides the teaching learning process more interisting and the students more to comprehend the speaking material and do every task from the researcher correctly. The result show both of the strategies pre-test and post-test significance values were obtained of 0.001 for the pre-test and 0.000 for the post-test. If this value is less than 0.05, it can be concluded that there is a significant difference and accepted.